Comparison of Carboxyhaemoglobin Concentrations between Low-flow and Minimal-flow Anaesthesia with Desflurane - Nazarudin B.; Khairulamir Z.; Azarinah I.; Jaafar MZ.; Karis M.; Esa K. (Department of Surgery, UKM Medical Centre, 2015)
This was a prospective randomised study comparing carboxyhaemoglobin concentrations between low-flow anaesthesia (fresh gas flow 1.0 L/min) and minimal-flow anaesthesia (0.5 L/min) using desflurane. Sixty (ASA 1 or 2) adult patients undergoing elective surgery under general anaesthesia were randomly allocated to receive either low-flow (Group 1) or minimal flow anaesthesia (Group 2). Venous blood samples for carboxyhaemoglobin levels were taken at baseline and at 10 mins intervals for 40 mins. Both groups showed significant increase in carboxyhaemoglobin concentrations within the first 10 mins when fresh gas flow of 4.0 L/min was used. Reduction in carboxyhemoglobin levels was seen after 20 mins of minimal or low flow anaesthesia. However, there was no significant difference in the magnitude of reduction of carboxyhemoglobin concentrations between the groups. The fractional inspired of oxygen (FiO2) showed no significant changes in either group. In conclusion, desflurane usage in anaesthesia with either low-flow or minimal-flow was not associated with increased carboxyhaemoglobin concentrations.